Застосування методу експериментального мутагенезу для овочевої кукурудзи - Куліш, О.Ю.; Погреблюк, М.В.; Ковальчук, З.В.; Бабич, В.О.; Парій, Я.Ф.; Симоненко, Ю.В.; Парій, М.Ф. (Фактори експериментальної еволюції організмів, 2016)
Aim. Mutation is the expansion of the genetic diversity of corn, which is the original material selection in the practice of
this culture. The purpose of our work was getting lines of vegetable maize with genetic mutations, which can be used to
improve the properties of vegetable corn, using chemical mutagens. Methods. In the research used a line of corn PА-3 and
samples 727 G, 708 A, 308 E A, B, 725. As a mutagen applied 5-bromuracil in 0.0191, 0.0955, 0.191, 0.573 and 1.91 g/l,
respectively, and sodium ozidum (NaN3
) – 1.95, 2.6 and 3.25 g/l. Results. It was obtained a new mutant line of vegetable
corn and it is characterized by complex economic and valuable features. Conclusions. We received a new subspecies of
the vegetable corn, which is promising for further research and production as a new generation of baby corn.
Keywords: Vegetable maize/corn, mutagenesis, mutations, baby corn.